Beyond legacy: Backstage stigmatisation and 'trickle-up' politics of urban regeneration. Issue 4 (July 2018) - Paton, Kirsteen
This article explores how stigmatisation is intimately linked with neoliberal governance and capital accumulation in specific ways through processes around the Glasgow Commonwealth Games. It advances the author's previous research exploring the effects of stigma on the East End community hosting the Games, by looking at some of the processes of power and profit which motivate stigmatising processes by 'gazing up', rather than 'gazing down'. That is, looking at the role of the stigmatisers in this project and not the stigmatised. It draws loosely on Goffman's concept of 'backstage' to shed light on those who produce and profit from these stigmatisation processes, including government bodies and actors and private business interests. Looking at some of the processes through which stigmatisation is profited from reveals not only forms of power vital to this process but that it is a key form of exploitation integral to capital accumulation. Under austerity, the political economy of the Games constitutes state support of private finance and a simultaneous withdrawal of social welfare support, which transfers the burden of debt from the state to the individual and wealth from public funds to private funds.